Analysis of Soil and Water Quality Status among the Different Villages in Kashi Vidyapith Block of Varanasi District, Uttar Pradesh - Prajapati, Pavan Kumar; Bharteey, Prem Kumar; Singh, Giriraj; Bahuguna, Ayush; Luthra, Nidhi; Pal, Sudhir; Sandilya, Niharika (International Journal of Bio-resource and Stress Management, 2024)
The current study was conducted from November, 2023 to June, 2024 in the villages of the Kashi Vidyapith block of Varanasi district, Uttar Pradesh (221 107), India to assess soil and water quality status. We have collected forty GPS (Global Positioning System)-based soil samples from depths of 0–15 cm and thirty water samples from the villages. The collected soil and water samples underwent analysis for physicochemical characteristics. The coefficient of variation for available nutrients fluctuated, with values for available nitrogen, phosphorus, potassium, sulphur, calcium, and magnesium recorded at 24.85%, 22.13%, 13.53%, 14.87%, 16.87%, and 16.40%, respectively. The nutritional index in the identified samples indicated that the amounts of available nitrogen, phosphorus, potassium, and sulphur were generally low. The water analysis revealed that the range of pH (7.6–8.8), electrical conductivity (EC) (0.56–2.33 dS m-1), chlorides (0.4–1.2 Meq l-1), carbonates and bicarbonates (0.4–1.2 Meq l-1 and 7.6–18.8 Meq l-1), while calcium and magnesium (5.8–75 Meq l-1). Additional, parameters such as permeability index (PI) range from 5.9–53.8 exceed permissible limits, whereas sodium (0.17–0.78 Meq l-1), potassium (0.02–2.89 Meq l-1), sodium adsorption ratio (SAR) (0.03–0.17 Meq l-1), soluble sodium percentage (SSP) (0.53–10 Meq l-1), potassium ratio (KR) (0.003–0.037), and residual sodium carbonate (RSC) (-60.6–4.6 Meq l-1) remain within permissible limits. Derivated from specific factors, the water quality index ranges from 153.43–444.23, suggesting a marginally unsustainable water quality. The integrated use of biofertilizers, bioinoculants, and site-specific nutrient management is essential for improving soil health and enhancing nutrient availability for plants.